Narrative Techniques as a Way to Represent the Reality in Crisis Media Texts - Olegovna, Popova Elena; Vladimirovich, Barabash Victor; Anatolievna, Chekunova Marina; Andreevich, Savastenko Roman; Vladimrovich , Kulikov Sergey; Vadimovna, Kharchenko Alina; Andreevna, Melnichenko Angelina (Journal of Ecohumanism, 2024)
This article discussed the using of narrative techniques in crisis situations. The authors emphasized that due to the narrative structure of human thinking, narrative can become a way to represent a crisis situation. The authors mentioned narrative techniques in the works of narrative researchers and ways how these techniques may affect emotions. The aim of the article was to identify techniques which the media use in coverage of crisis situation and determined the purpose of using these techniques. For this aims the authors used the descriptive method and the method of content analysis, narrative analysis. More than 150 materials from “The Guardian”, “The Washington Post”, “Expert”, “Izvestia” were analyzed in this article. An analysis of the materials shown that narrative techniques are often used by journalists. In American and English press journalists included narrative in their materials to evoke emotions. In Russian press narrative techniques were used to present a picturesque scene of what is happening and immerse the reader in the situation. Authors have found out that narrative techniques in covering crisis situations is used to express the author’s assessment, to evoke emotions and as an attempt to give own interpretation to the crisis. Contribution: The contribution of the research is in the contemporary role of the political agenda. Different media interpret the events of the crisis in different ways and researching the methods they use helps to determine the degree of their objectivity and the goals they want to achieve.